Anisotropy in conventional and uniaxially thermoformed auxetic polymer foams. (15th May 2022) - Zhang, Qicheng; Yu, Xindi; Scarpa, Fabrizio; Barton, David; Rankin, Kathryn; Lang, Zi-Qiang; Zhang, Dayi
Abstract: Auxetic (negative Poisson's ratio) open cell polymeric foams have been traditionally produced using thermoforming techniques coupled with the volumetric compression of conventional (pristine) off-the-shelf foams. The anisotropy of the pristine foam plays however a strong role on the performance of thermoformed auxetic foams, and this is the subject studied in this work. Micro computed tomography (μ-CT) scans indeed show that the cell structures of the pristine foam exhibit an elongated convex polyhedron shape, with more ribs oriented along the foam rising direction d1 . The modulus along d1 can be up to 70% larger than the one along the transverse directions, and the Poisson's ratios in different planes are also noticeable different, ranging from 0.2 to 0.85. Three types of auxetic foams uniaxially thermoformed along the three orthogonal directions of the conventional porous material are here developed, and all show different mechanical performances due to the anisotropy of the conventional baseline foam. The auxetic foams show significant auxetic behavior along the thermoforming direction only when thermoformed along the transverse directions of the pristine foam (d2 or d3 ) and loaded along the foam rising direction (d1 ); in that case, the negative Poisson's ratio reach values as low as −1. In other cases, the auxetic performance is not evident, and the Poisson's ratio is close to 0. Finite Element models of the pristine and auxetic foams have been also here developed based on the 3D models from μ-CT, and the stiffness-strain curved derived from those coincide well with the experimental results. The simulated deformation mechanisms of the cell structures inside different foams help to explain the anisotropic performance of the foams and the differences between compressive and tensile properties.